The Effect of Circuit Training and Fartlek Training on the VO₂max of Handball Athletes - Muhammad Fadli; Andi Muhammad Rizky Al Mufarid; Sitti Fatimah Azzahra M; Wilda Yati; Muhammad Rizky Alfarizi (CV Lentera Cendekia Indonesia, 2025)
This research is an experimental research type that uses a